Mário Faustino night engineering in O homem e sua hora, reading the poem “Mito” - Cavalcanti, Luciano (fólio - revista de letras, 2019)
Mário Faustino, poet in the generation of 1950, established a direct relationship with the modern tradition of Western poetry. In which we see a strong trend to circumvention of the ordinary world and the importance of artisanal labor to the construction of the poem. In this perspective, we in this study, dedicate our efforts on analyzing the poem “Mito”, in the book O homem e sua hora. To do so, you must observe the relationship undertaken by the poet between myth and poetry, as well as the fruitful dialogue that Mario Faustino established with surrealism, one of the most important aesthetic trends of the European avant-garde of the XX century.